ZnO Nanoparticles Synthesis and Characterization by Hydrothermal Process for Biological Applications - Wirunchit, Supamas; Koetniyom, Wantana (My University, 2023)
This research is interested in the development of zinc oxide (ZnO) nanoparticle synthesis by hydrothermal precipitation solutions for biological applications. The synthesis of ZnO nanoparticles study from zinc nitrate (Zn(NO3)2) precursor under the three precipitator solutions consists of potassium hydroxide (KOH), sodium hydroxide (NaOH), and ammonium hydroxide (NH4OH), respectively. The synthesis of ZnO nanoparticles is investigated using the following techniques: X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and Raman spectroscopy techniques. The structure and size of the ZnO nanoparticles are analyzed by using a field emission scanning electron microscope (FE-SEM), and finally, the antibacterial efficacy of the ZnO nanoparticles is studied. The hydrothermal synthesis condition realizes that the smallest ZnO nanoparticles come from the zinc nitrate (Zn(NO3)2) precursor reacted with sodium hydroxide (NaOH) precipitator at 120 °C for 4 h.
Keywords: biological applications; hydrothermal; precipitator; precursor; ZnO nanoparticles